Collecting High Frequency Panel Data in Africa Using Mobile Phone Interviews - Croke, Kevin (World Bank, Washington, DC, 2012)
As mobile phone ownership rates have risen in Africa, there is increased interest in using mobile telephony as a data collection platform. This paper draws on two pilot projects that use mobile phone interviews for data collection in Tanzania and South Sudan. The experience was largely a success. High frequency panel data have been collected on a wide range of topics in a manner that is cost effective, flexible (questions can be changed over time) and rapid. And once households respond to the mobile phone interviews, they tend not to drop out: even after 33 rounds of interviews in the Tanzania survey, respondent fatigue proved not to be an issue. Attrition and non-response have been an issue in the Tanzania survey, but in ways that are related to the way this survey was originally set up and that are fixable. Data and reports from the Tanzania survey are available online and can be downloaded from: www.listeningtodar.org.